Exploring Impulsive Buying Tendency in Preloved Goods with Mindful Consumption and Platform Trust - Anita Dwi Fitriani; Rita Ambarwati (Bina Nusantara University, 2026)
The research examined the influence of mindful consumption, ego involvement, platform trust, and product involvement on buying intentions toward preloved goods, with impulsive buying tendency as a mediating variable. The novelty of the research lay in extending the Theory of Planned Behavior (TPB) by integrating impulsive buying tendency to explain consumer behavior in the Indonesian preloved market, which remained underexplored. A quantitative approach was employed by distributing questionnaires to 322 respondents who had purchased preloved items. Samples were selected using a simple random sampling technique, ensuring that every consumer in the population had an equal chance of being included. Then, data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. The results show that ego involvement and platform trust significantly and positively influence buying intentions, while mindful consumption and product involvement do not have a direct effect. However, both variables indirectly influence buying intentions through impulsive buying tendency, which serves as a significant mediator. These findings indicate that consumer decisions in the preloved market are shaped not only by rational considerations but also by emotional impulses and trust in sales platforms. Theoretically, the research enriches TPB by highlighting the impulsive buying tendency as a mediating construct in sustainable consumption. Practically, the results suggest that platform managers should strengthen consumer trust through transparency and secure transactions, while marketers can combine sustainability messages with emotional strategies to enhance buying intentions.